Robust Regression on Simple Housing Environmental Performance Measurement - Hrp, Hafizah Miranda Putri; Nababan, Esther Sorta Mauli; Tulus (Sinkron : jurnal dan penelitian teknik informatika, 2024)
Robust regression in residential environmental performance measurement can provide significant benefits. This method can help identify and overcome uncertainties in measurement results so that decision making related to environmental protection and management can be done more accurately. This type of research is quantitative with a descriptive approach. The results of this study indicate that the results of the M-estimate robust regression estimation on simple housing environmental performance obtained the M-estimate robust regression equation, namely ŷ = 15.562+0.476X1-0.453X2+0.222X3-0.427X4. Based on the p-value test results, it shows that population attributes, house attributes, energy consumption volume and utilities and services have a significant effect on environmental performance. The results of the hypothesis testing of the M-estimation robust regression method on the environmental performance of simple housing obtained that the variables of population attributes and energy consumption volume have a positive and significant effect on environmental performance while the variables of house attributes and utilities and services have a negative and significant effect on environmental performance.